Prevalence of tuberculosis in Ethiopia: an umbrella review of systematic review and meta-analysis - Abebe, Wagaw; Gedifie, Solomon; Emagneneh, Tadele (Frontiers in Public Health, 2025)
BackgroundTuberculosis is one of infectious disease, which caused by mycobacterium tuberculosis. It is still one of the major problems threatening public health worldwide. However, there are inadequate systematic studies and statistical assessments of tuberculosis prevalence, mainly in Ethiopia.ObjectiveThis umbrella review aimed to determine the prevalence of tuberculosis across the country.MethodsIn accordance with standard review principles, a systematic search was conducted on Web of Science, PubMed, Science Direct, and Google Scholar to find pertinent studies. For the final umbrella review, a total of eleven relevant studies on tuberculosis prevalence were found. Data was extracted using Microsoft Excel with separate sheets for tuberculosis. The extracted data was analyzed with STATA software version 17.0. A sensitivity analysis was carried out to assess the role of each study in the final results. The Egger’s test and a funnel plot were used to assess the existence of publication bias. Trim and fill analysis were used for determining a bias-adjusted effect estimate. Inverse of variance statistics were used to assess heterogeneity among studies. If the I2 value was ≥50%, significant heterogeneity was identified, and subgroup analysis was carried out.ResultsThis umbrella review includes 11 studies. In this review, the pooled prevalence of tuberculosis was 12.81% (95% confidence interval, 5.07–20.55). The subgroup analysis based on sample size and number of studies revealed significant variations in the pooled tuberculosis prevalence.ConclusionThis comprehensive study revealed that tuberculosis is widespread in Ethiopia. The observed increase in tuberculosis incidence emphasizes the important need for improved infection prevention and monitoring systems to reduce tuberculosis burden and transmission in Ethiopia. Furthermore, collaboration at the local, national, and international levels is required to address the factors that lead to tuberculosis and mitigate its impact on public health. Additionally, it provides crucial information to Ethiopian government officials and administrators.